Combining reactive transport modeling with geochemical observations to estimate the natural gas hydrate accumulation. (1st October 2020) - Tian, Hailong; Yu, Ceting; Xu, Tianfu; Liu, Changling; Jia, Wei; Li, Yuanping; Shang, Songhua
Highlights: Reactive transport was coupled with the behavior of hydrate-bearing system. A novel approach for constraining results of long-term simulations was proposed. The methane-hydrate amount of a specific site was accurately estimated. Methane sources for hydrates were quantified using reactive transport simulations. Abstract: Predicting the distribution and resource of gas hydrates and understanding gas hydrate forming mechanisms are critical for assessing natural gas hydrate exploration potential, as well as exploiting hydrates. This study aims to provide a portable solution for evaluating resource of natural gas hydrate and quantifying contribution of methane sources via numerical simulations constrained by site-specific data. To numerically describe the complex process of biogenic methane production, an integrated simulation package, TOUGH + Hydrate + React (TOUGH + HR), was developed by coupling reactive transport, biodegradation and deposition of organic matter with behavior of hydrate-bearing system. Based on observed data from site SH2 in the South China Sea, a growing one-dimensional column model was constructed, and simulated via the developed TOUGH + HR tool. The results showed that when considering biogenic methane was the only source for hydrate, simulated maximum saturation of hydrate reached ~ 0.19, which is much lower than the observed value (~0.46), suggesting that the in-situ biogenic methane is not enough to form the high-saturation hydrate. When the upward flux of methane (considered as thermogenic methane) increased to 1.00 × 10 −11 k g · m - 2 · s - 1, both simulated saturation and distribution of hydrates matched the observed data well, including the profile of remained total organic carbon (TOC), the location of interface between dissolved methane and sulfate (SMI), and the derived chlorinity. Simulation results suggest that the ratio of biogenic methane to thermogenic methane forming hydrates was about 1:3. Predicted amount of methane hydrate using the column model was 3258.33 kg, very close to the estimated based on field observation (3112.82 kg).